Risikomanagement, Organisation, Compliance für Unternehmer - Zenke, Ines; Zenke, Ines; Schäfer, Ralf; Schäfer, Ralf; Brocke, Holger; Brocke, Holger (De Gruyter Praxishandbuch, 2015)
Risk management, risk controlling, internal audits, compliance, corporate organization: this book aims to provide an integrated presentation of the concept of risk by bringing together practical knowledge from all of these sub-areas, illustrating their interactions, and demonstrating meaningful correlations. It is written by practitioners for practitioners.